Qur’anic reflections on moral crisis and their implications for character-based islamic education - Syafri, Ulil Amri; Sun’an, Saodah Bte; Bahar, Herwina; Rofiq, Aunur (Tawazun: Jurnal Pendidikan Islam, 2026)
This article analyzes the relationship between religion and power and its implications for moral crisis from the perspective of Qur’anic civilization, positioning the narrative of the Children of Israel as an ethical reflection across time. The study employs a qualitative-conceptual approach through thematic exegesis (maudhu‘i), historical-critical analysis, and civilizational ethical reflection to understand patterns of deviation from revealed values within social dynamics. The findings indicate that moral decline is not merely an individual problem but a civilizational crisis that emerges when religion is reduced to a symbol of identity and a tool for legitimizing power, thereby weakening the values of justice, trustworthiness (amanah), and social responsibility. Qur’anic reflection reveals patterns of deviation manifested in ritual formalism, manipulation of religious authority, and the neglect of moral integrity. Similar phenomena are evident in contemporary contexts, marked by. thical disorientation in public life and the erosion of social responsibility. This study emphasizes that Islamic education grounded in Qur’anic values—such as tawhid, honesty, trustworthiness, and justice—plays a strategic role in cultivating ethical character and social integrity. Thus, the reflection on Qur’anic civilization provides an ethical foundation for strengthening character education through an integrative approach that unites spirituality, moral conduct (akhlaq), and human responsibility. Abstrak Artikel ini menganalisis relasi agama dan kekuasaan serta implikasinya terhadap krisis moral dalam perspektif peradaban Qur’ani, dengan menempatkan narasi Bani Israil sebagai refleksi etis lintas zaman. Penelitian menggunakan pendekatan kualitatif-konseptual melalui tafsir tematik (maudhu’i), kajian historis-kritis, dan refleksi etika peradaban untuk memahami pola penyimpangan nilai wahyu dalam dinamika sosial. Hasil kajian menunjukan bahwa kemerosotan moral bukan sekadar persoalan individual, melainkan krisis peradaban yang muncul ketika agama direduksi menjadi simbol identitas dan legitimasi kekuasaan, sehingga melemahkan nilai keadilan, amanah, dan tanggung jawab sosial. Refleksi Qur’ani memperlihatkan pola penyimpangan melalui formalisme ritual, manipulasi otoritas keagamaan, dan pengabaian integritas moral. Fenomena serupa tampak dalam konteks kontemporer, ditandai disorientasi etika publik dan melemahnya tanggung jawab sosial. Studi ini menegaskan bahwa pendidikan Islam berbasis nilai Qur’ani—seperti tauhid, amanah, kejujuran, dan keadilan—memiliki peran strategis dalam membangun karakter beradab dan integritas sosial. Dengan demikian, refleksi peradaban Qur’ani memberikan landasan etis bagi penguatan pendidikan karakter yang integratif antara dimensi spiritual, akhlak, dan tanggung jawab kemanusiaan.